The permanent temperature monitoring for flow rate quantification in production and injection wells - M. I. Kremenetskiy; V. M. Krichevsky; V. V. Solovieva; A. N. Nikonorova (Georesursy, 2024)
A technique for monitoring of a production well rate dynamics based on the results of long-term temperature measurements in the wellbore at a certain depth which is significantly higher than the productive formation in real time is presented. The proposed analytical approaches for the well rate evaluation are based on the classical temperature behavior in the intervals of liquid and gas movement along the wellbore at a relatively far from the target formations. The temperature gradient in such intervals practically does not change with time and is close to geothermal, regardless of whether the inflow or injection is stable over time, or the well is in an unstable and cyclic production. It makes possible to find a relationship between the temperature change and heat flux density on the wellbore with simple and clear analytical approach, and to associate the heat flux density dynamics with the flow rate of the fluid moving along the wellbore. The main novelty of the presented publication is the justification of temperature deconvolution application for well rate changes vs time evaluation on a substantially non-stationary well production or injection conditions. The presented approach of permanent temperature monitoring interpretation is applicable not only for cases of step well rate changes, but also for cases of gradual well rate changes vs time. A wide range of measuring sensors can be used for presented approach implementation, including permanent fiber-based distributed along the length of the wellbore systems.